A Study on Application of SPAR-H Method for Human Reliability Analysis of an Electric-electronic System of a Mechanism for Moving a Nuclear Fuel Irradiation Capsule - Eduardo Tadeu Stehling Saraiva; Vanderley Vasconcelos; Daniel Almeida Magalhães Campolina; Alessandra Lopes de Carvalho (Brazilian Journal of Radiation Sciences)
The “Centro de Desenvolvimento da Tecnologia Nuclear” (CDTN) is developing the prototype of a computer-controlled mechanism for moving a nuclear fuel irradiation capsule, called “Dispositivo de Movimentação da Cápsula” (DMC). This mechanism will be installed in the “Reator Multipropósito Brasileiro” (RMB), which is a Brazilian research reactor currently under construction, and will be used to carry out fuel qualification tests, such as power ramp tests. In addition to the engineering design of the mechanical system, CDTN is also developing the engineering design of the DMC electric-electronic system including a control and data acquisition software. In the context of nuclear facilities, human factors play an important role in safety and reliability assessments. Many techniques are suitable for modeling and analyzing human reliability and, among these, can be highlighted “Standardized Plant Analysis Risk‑Human Reliability Analysis (SPAR‑H)”. In this work, the applicability of this technique to predict human error probabilities (HEPs) is illustrated as an example of a quantitative study to improve the safety and reliability of the DMC electric-electronic system through acting on human factors issues.